2015
DOI: 10.1093/ofid/ofv162
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Human Immunodeficiency Virus-Hepatitis B-Hepatitis C Point-of-Care Tests Improve Outcomes in Linkage-to-Care: Results of a Randomized Control Trial in Persons Without Healthcare Coverage

Abstract: In this randomized-control trial, conducted at a free clinic in France for predominately immigrant populations without healthcare, we demonstrate that simultaneous HIV/HBV/HCV point-of-care rapid testing improves screening outcomes. Increased awareness of infection status likely helped link these patients to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…In a systematic review of the effectiveness of interventions to improve hepatitis C testing among PWID, on‐site testing with pre‐test discussion and education and dried blood spot (DBS) testing were demonstrated to be effective in increasing hepatitis C testing among PWID when compared to control interventions . Other strategies that have been evaluated (without any comparator intervention) include physical and electronic medical chart reminders to prompt targeted risk‐based assessment and testing, peer‐delivered outreach hepatitis C testing and hepatitis C education, prison‐based outreach testing, patient referral contact tracing with monetary incentive for testing and point‐of‐care hepatitis C testing . Decisions on what intervention(s) to implement to enhance hepatitis C testing will depend on the setting (and prevalence of hepatitis C infection), the model of care, the local context and health care system.…”
Section: Interventions To Enhance Hepatitis C Prevention Testing Andmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of the effectiveness of interventions to improve hepatitis C testing among PWID, on‐site testing with pre‐test discussion and education and dried blood spot (DBS) testing were demonstrated to be effective in increasing hepatitis C testing among PWID when compared to control interventions . Other strategies that have been evaluated (without any comparator intervention) include physical and electronic medical chart reminders to prompt targeted risk‐based assessment and testing, peer‐delivered outreach hepatitis C testing and hepatitis C education, prison‐based outreach testing, patient referral contact tracing with monetary incentive for testing and point‐of‐care hepatitis C testing . Decisions on what intervention(s) to implement to enhance hepatitis C testing will depend on the setting (and prevalence of hepatitis C infection), the model of care, the local context and health care system.…”
Section: Interventions To Enhance Hepatitis C Prevention Testing Andmentioning
confidence: 99%
“…Integrated hepatitis C care within drug use and psychiatric services delivered by a multidisciplinary team with case management services, with or without non‐invasive liver disease assessment, was associated with improved hepatitis C treatment uptake . Other strategies evaluated and shown to enhance hepatitis C linkage to care and treatment include dried blood spot testing, point‐of‐care hepatitis C testing, non‐invasive liver disease screening using transient elastography (FibroScan ® ) with facilitated referral to care, integrated hepatitis C care, patient navigation programmes, peer‐based support, financial incentive programmes and telemedicine . However, the majority of interventions that have been evaluated are specific for the interferon‐era.…”
Section: Interventions To Enhance Hepatitis C Prevention Testing Andmentioning
confidence: 99%
“…Potential strategies to improve HCV testing include education and counseling by health professionals with on-site HCV testing (Cullen et al, 2006; Lacey, Ellen, Devlin, Wright, & Mijch, 2007; Meyer et al, 2015; Rosenberg et al, 2010; Sahajian et al, 2011; Zhou et al, 2016), physical and electronic medical chart reminders to prompt targeted risk-based assessment and testing (Drainoni et al, 2012; Krauskopf et al, 2014; Litwin et al, 2012; Meyer et al, 2015; Zhou et al, 2016), and simplified testing, including dried blood spot testing (Abou-Saleh, Rice, & Foley, 2013; Coats & Dillon, 2015; Craine, O'Toole, D'Arcy, & Lyons, 2009; Hickman et al, 2008; McLeod et al, 2014; Meyer et al, 2015; Tait, Stephens, McIntyre, Evans, & Dillon, 2013; Zhou et al, 2016), and point-of-care HCV testing (Beckwith et al, 2016; Bottero et al, 2015; Morano et al, 2014). …”
Section: Hcv Testingmentioning
confidence: 99%
“…Simplified HCV testing, including dried blood spot testing (McAllister et al, 2014) and point-of-care HCV testing (Bottero et al, 2015; Morano et al, 2014) has been shown to facilitate linkage to HCV care. Other strategies that have been demonstrated to facilitate linkage to HCV care and treatment include, non-invasive liver disease screening using transient elastography (FibroScan ® ) with facilitated referral to care (Foucher et al, 2009; Marshall et al, 2015; Moessner et al, 2011), integrated HCV care (Cullen et al, 2006; Evon et al, 2011; Ho et al, 2015; Knott et al, 2006; Masson et al, 2013; Zhou et al, 2016), patient navigation programs (Falade-Nwulia et al, 2016; Trooskin et al, 2015), and telemedicine (Arora et al, 2011; Lloyd et al, 2013; Mashru, Kirlew, Saginur, & Schreiber, 2017; Tahan, Almashhrawi, Kahveci, Mutrux, & Ibdah, 2016).…”
Section: Linkage To Hcv Care and Treatmentmentioning
confidence: 99%
“…Applying lessons learned from annual syphilis screening efforts in HIV when considering annual HCV testing in HIV-infected MSM, could improve opportunities to identify and cure incident cases in HIV-infected persons [80]. Because most persons with HCV and HBV infection and 15–30% of those with HIV-infection in the US and Europe remain undiagnosed, increased uptake of simultaneous point-of-care testing for HIV, HCV, and HBV in high-risk populations merits consideration [81]. While emergency rooms represent an opportunity to increase HCV and HIV diagnoses through opt-out testing [82], barriers to linkage to care persist and require dedicated resources [83].…”
Section: Diagnosis Cost and Accessmentioning
confidence: 99%